SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/102383-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gas Productivity Using Alcoholic Acids: Laboratory and Field Studies

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe objectives of this study were to: investigate effectiveness of alcoholic acids to stimulate Devonian sandstone gas reservoirs, determine the optimum acid formulation, and recommend the best practices to enhance stimulation treatments in gas wells. In this study, extensive coreflood experiments were conducted on sandstone cores recovered from gas reservoirs to assess the effectiveness of various acid formulations (HCl, HCOOH, HCl/HF, and HCOOH/HF, with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…When the dewpoint pressure is reached, the drop in pressure is sudden in both cases, but is still less in the fractured case. Al-Hashim and Hashmi (2000) found that gas-and liquid-production rates for the fractured case stabilize at a rate that is more than three times that of the nonfractured stabilized rate, with extended duration of the pressure plateau above the dewpoint. One of the main problems that may result in poor performance of hydraulically fractured wells is the accumulation of liquid condensate around the fracture's walls.…”
Section: Hydraulic Fracturingmentioning
confidence: 93%
See 2 more Smart Citations
“…When the dewpoint pressure is reached, the drop in pressure is sudden in both cases, but is still less in the fractured case. Al-Hashim and Hashmi (2000) found that gas-and liquid-production rates for the fractured case stabilize at a rate that is more than three times that of the nonfractured stabilized rate, with extended duration of the pressure plateau above the dewpoint. One of the main problems that may result in poor performance of hydraulically fractured wells is the accumulation of liquid condensate around the fracture's walls.…”
Section: Hydraulic Fracturingmentioning
confidence: 93%
“…A combination of acidizing treatments and the additions of solvents (alcohols) was described before by Al-Anazi et al (2006). The main objective of adding alcohol is to reduce the interfacial tension between the spent acid and gas, which allows for better removal of the liquid that fills the wormhole, while at the same time enhancing the gas permeability following the acidstimulation treatment.…”
Section: Combination Of Different Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol is the most common solvent used in field applications. Methanol displacement of liquid accumulations is attributed to the multi-contact-miscible technique [9]. Considerable enhancement in the relative permeability to gas are reported by using methanol injection for both sandstone and carbonate reservoirs [10,11].…”
Section: Introductionmentioning
confidence: 99%